Attitudes of mathematics teachers at the secondary stage in the Kingdom of Saudi Arabia towards teaching in light of the skills of the eleventh century - Al-Abdullah, Abdulmoniem Ali (Journal of Educational and Psychological Sciences, 2021)
The aim of the research was to explore the attitudes of mathematics teachers at the secondary stage of teaching in light of the skills of the twenty-first century, and the descriptive survey method was used. A questionnaire of “twenty-first century skills for mathematics teachers” was prepared that consisted of (22) items that were applied to a sample of (60) Male and female teachers, from different regions of the Kingdom, and the results showed that the teaching performance obtained a general average (4.0 out of 5.0), with a degree of importance (very important), and at the level of learning models, the "self-organization" model obtained the highest average (4.22), followed by a model. Collaborative work with an average of (4.20), followed by the model of “using technology in education” with an average of (4.18), followed by the two models “problem-solving and innovation in the real world and methods of skillfully presenting and communicating” with an average of (4.14), and finally the “building knowledge” model With an average of (3.11), and based on the results, the researcher presented a number of recommendations and proposals to develop the teaching performance of mathematics teachers at the secondary level in light of the skills of the twenty-first century.